Marbles, Quarries and Workshops on the Highlands of Northern Macedonia - Niewöhner, Philipp; Audley-Miller, Lucy; Prochaska, Walter (Archäologischer Anzeiger, 2017)
Throughout antiquity the landlocked highlands of northern Macedonia employed various local and imported marbles. Among them a certain fine-grained white dolomite stands out both in number of artefacts and in quality of workmanship. The material was used for Roman sculptures as well as the best carvings from Late Antiquity and can be traced back to an ancient quarry at Sivec near Prilep. Local workshops must have been based there or at nearby cities. This contrasts with the southern lowlands south of the Demir Kapija Gorge, where Thasian marble appears the default white marble preference and could be imported with relative ease via the Axios/Vardar River. In Late Antiquity, Sivec marble started to be carved in a style and quality that is without precedent in the region, but often indistinguishable from the production of the quarries and workshops at Proconnesus/Constantinople and Docimium in Anatolia. The three Late Antique quarries seem to have been interconnected in a way that is reminiscent of and possibly in part based on the Roman quarry system. archaeometry • FYROM • Late Antiquity • Sivec dolomite • Stobi